The Effect of Mangosteen Peel Extract (Garcinia mangostana Linn.) on the Production of Escherichia coli Bacterial Biofilm Causing Urinary Tract Infections - Ryan Maulana Ardhana; Wiwin Retnowati; Danti Nur Indiastuti; Nurul Wiqoyah; Wilda Mahdani (Majalah Biomorfologi, 2026)
Background: Biofilm formation by Escherichia coli is a key factor contributing to chronic infections, particularly urinary tract infections and antibiotic resistance. Mangosteen peel (Garcinia mangostana Linn.) contains bioactive compounds that have potential as natural antibiofilm agents. Objective:  To examine how mangosteen peel extract at varying concentrations affected biofilm production of Escherichia coli in vitro. Materials and Methods:  This true experimental study using post-test control group design employed mangosteen peel extract concentrations of 0.15%, 0.10%, 0.05%, 0.025%, and 0.0125%. A clinical isolate of Escherichia coli from a urine specimen was used in this study. The authors conducted the test using a microtiter plate assay and biofilm development. ELISA reader was employed to measure the optical density (OD) at 492 nm. Furthermore, this study employed the Shapiro-Wilk test, the homogeneity test, and the Kruskal-Wallis test to assess the data. Results: The results indicated a decrease in OD values across all treatment groups compared to the negative control, suggesting a trend of reduced biofilm formation. The homogeneity test indicated equal variances across groups. Therefore, non-parametric Kruskal-Wallis test was used to test the hypothesis. This statistical analysis revealed that the decrease of the biofilm thickness was not statistically significant (p > 0.05). Conclusion:  Mangosteen peel extract demonstrates potential as a natural antibiofilm agent against Escherichia coli, although its effect was not statistically significant at the tested concentrations. Therefore, further studies should investigate fractionated active compounds and higher concentrations to determine optimal antibiofilm activity.